THE LANGUAGE OF NARCISSISTIC TENDENCIES IN YOUTUBE USERS A PSYCOPRAGMATIC ANALYSIS - Putra, Afdalil Aflika; Rahmat, Wahyudi; Tatalia, Ricci Gemarni (ppjbsip, 2021)
This research is motivated by the videos uploaded on Andre Taulany's youtube which tend to have the language of someone who has a narcissistic tendency. so that it can be seen from the expressiveness of the language. This research will be discussed in a psychopragmatic study. This approach is deliberately used to examine expressive speech acts that are motivated by a person's psychology and psychological factors such as one's desire, willingness and desire to get something. The type of research used in this research is qualitative research. The data in this study are the words conveyed by Andre Taulany in the video on his youtube account based on the number of views and comments. Data were collected by using listening and note-taking techniques. Data analysis using the matching method and the agih method. speech acts that convey the contents of Andre's thoughts or feelings that are expressed or shown through his expressive language. The utterances that Andre expressed through his expressive language lead to the characteristics of someone who has narcissistic tendencies.